2000
DOI: 10.1034/j.1398-9995.2000.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4‐independent production of Th2 cytokines by nasal lymphocytes and nasal eosinophilia in murine allergic rhinitis

Abstract: These results indicate that although IL-4 is necessary for the production of Th2-associated antibodies--in particular, IgE--it is not required for either the production of the Th2-associated cytokines IL-5 and IL-10, or the induction of nasal eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
4
20
0
1
Order By: Relevance
“…Thus, our results indicate that signals mediated by CRTH2 selectively enhance Th2-type Ab production. The decreased production of IL-4 by submandibular lymph node cells from CRTH2 Ϫ/Ϫ mice in response to Cry j 1 restimulation supports this result because IL-4 plays a critical role in IgE synthesis in vivo (37). Although whether CRTH2 activation directly leads to IL-4 production in mice remains unclear, recent investigations have demonstrated that PGD 2 causes the preferential induction of IL-4 production by Th2 cells in humans by binding to CRTH2 (38,39).…”
Section: Discussionsupporting
confidence: 56%
“…Thus, our results indicate that signals mediated by CRTH2 selectively enhance Th2-type Ab production. The decreased production of IL-4 by submandibular lymph node cells from CRTH2 Ϫ/Ϫ mice in response to Cry j 1 restimulation supports this result because IL-4 plays a critical role in IgE synthesis in vivo (37). Although whether CRTH2 activation directly leads to IL-4 production in mice remains unclear, recent investigations have demonstrated that PGD 2 causes the preferential induction of IL-4 production by Th2 cells in humans by binding to CRTH2 (38,39).…”
Section: Discussionsupporting
confidence: 56%
“…The IL-5 producers outnumbered the IL-4 producers, consistent with the fact that these cytokines are frequently not coexpressed by T cells (47,48). This dissociation of "Th2" cytokines is not surprising because IL-4 and IL-5 expression by T cells underlies independent instructed differentiation and different gene regulation pathways (48,49).…”
Section: Discussionmentioning
confidence: 72%
“…Early interleukin (IL)-4 and thymic stromal lymphopoietin (TSLP) produced by basophils in response to allergens with protease activity may contribute to Th2 differentiation [12]. Th2 cells produce IL-4/IL-13 and express CD40L, which promote the class-switching of B cells to immunoglobulin (Ig)E [13,14]. When sensitized subjects inhale antigens, the antigens pass through the epithelial tight junctions in the nasal mucosa to bind IgE on the surface of mast cells in the epithelial layer of the nasal mucosa, inducing the release of chemical mediators including histamine, prostaglandins and cysLTs by aggregation of FceRI.…”
Section: Introductionmentioning
confidence: 99%